Role of aryl hydrocarbon receptor in toxic effects of emerging environmental pollutants - Mingxuan ZHANG; Baoqiang FU; Jinhao LI; Kang WANG; Yan JIANG; Tao CHEN (环境与职业医学)
In recent years, an increasing number of emerging environmental pollutants have been identified, garnering widespread attention. Many of these pollutants are characterized by their environmental persistence and bioaccumulation, which pose significant threats to both the ecological environment and human health. However, the molecular mechanisms underlying their effects remain unclear, limiting our ability to assess their adverse impacts and develop effective protective measures. The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor traditionally known to be activated by dioxins and polycyclic aromatic hydrocarbons (PAHs) and is involved in the metabolism of exogenous chemicals. Recent research has shown that the AHR can be activated by a diverse range of exogenous and endogenous chemicals and participates in various biological processes. Studies have demonstrated that AHR mediates the toxic effects of emerging environmental pollutants such as perfluorooctane sulfonamide (PFOSA) and N-(1,3-dimethylbutyl)-N’-phenyl-p-phenylenediamine quinone (6PPDQ). This paper provided an overview of the AHR activation and the toxic effects induced by emerging environmental pollutants, with a focus on how the AHR activation interacts with multiple signaling pathways. The significance of these interactions in environmental risk assessment and toxicological research was also discussed. We aim to provide a scientific basis for environmental protection and risk assessment.